2014
DOI: 10.3748/wjg.v20.i32.11116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of innate immune receptors and infections after liver transplantation

Abstract: Infection is the leading cause of complication after liver transplantation, causing morbidity and mortality in the first months after surgery. Allograft rejection is mediated through adaptive immunological responses, and thus immunosuppressive therapy is necessary after transplantation. In this setting, the presence of genetic variants of innate immunity receptors may increase the risk of post-transplant infection, in comparison with patients carrying wild-type alleles. Numerous studies have investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 167 publications
0
12
0
Order By: Relevance
“…Four further articles were manually identified from reference lists. After removing of duplicate studies and detailed evaluation of titles and abstracts, 45 articles were fully assessed for eligibility . Eleven studies (Table ) fulfilled the inclusion and exclusion criteria and were finally included in the present study (PRISMA flow chart shown in Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four further articles were manually identified from reference lists. After removing of duplicate studies and detailed evaluation of titles and abstracts, 45 articles were fully assessed for eligibility . Eleven studies (Table ) fulfilled the inclusion and exclusion criteria and were finally included in the present study (PRISMA flow chart shown in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic susceptibility to infection among SOT recipients appears to be driven by a number of allelic variants in genes orchestrating innate and adaptive immune responses, whose clinical impact may be at least partially unmasked by the effect of posttransplant immunosuppression. In the present meta‐analysis comprising 11 studies and more than 1800 SOT recipients we observed that, as compared to high‐MBL expression haplotypes (YA/YA or YA/XA), the risk of posttransplant bacterial and fungal infections significantly increases by 30% in the presence of any MBL‐deficient haplotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations